2006
DOI: 10.1002/j.2050-0416.2006.tb00704.x
|View full text |Cite
|
Sign up to set email alerts
|

Staling in Two Canned Lager Beers Stored at Different Temperatures - Sensory Analyses and Consumer Ranking

Abstract: Two canned lagers, lager A (5% abv with late hop character) and lager B (4% abv) stored for 0, 7, 14, 21 and 28 days at 4, 12, 30 and 37°C were scored by trained sensory assessors (10) for liking and stale and related attributes of : cabbagy, cardboard, catty, grainy, honey, leathery, metallic, musty, skunky, and sour. Principal component analysis explained 80% data variance in 3 significant (p < 0.05) and 75% in 4 significant factors for A and B, respectively. In both lagers, aging correlated significantly w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
(22 reference statements)
0
6
1
Order By: Relevance
“…Although the concentration of the aldehydes increased in a direct relationship with time and also storage temperature in lager A, this was not observed with lager B. In the sensory data from this study 15 , the score for sensory stale character for B showed a second minimum. This suggested that differences between the beers related to style, original gravity, ethanol content, composition and Fig.…”
Section: Discussioncontrasting
confidence: 60%
See 4 more Smart Citations
“…Although the concentration of the aldehydes increased in a direct relationship with time and also storage temperature in lager A, this was not observed with lager B. In the sensory data from this study 15 , the score for sensory stale character for B showed a second minimum. This suggested that differences between the beers related to style, original gravity, ethanol content, composition and Fig.…”
Section: Discussioncontrasting
confidence: 60%
“…In the sensory data from this study 15 , the score for sensory stale character for B showed a second minimum. This suggested that differences between the beers related to style, original gravity, ethanol content, composition and Fig.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations